Current Change of 12 Volt DC to 220 Volt AC Using Inverter Circuit - M Khoirul Muslikin (Publikasi Indonesia, 2026)
The need for reliable alternative sources of electricity continues to increase, especially in areas that are not yet reached by PLN's network and in renewable energy systems based on solar panels and batteries. Inverters play a key role in such systems because they convert DC voltage into AC that household appliances need. This study aims to design and test a simple inverter circuit capable of converting 12 Volt DC voltage into 220 Volt AC voltage. The inverter was designed using a 12V battery source, D313 transistor as an electronic switching component, and a center tap transformer as a step-up transformer. The research method used was an experimental method through stages of circuit design, assembly, testing, and analysis of inverter performance using LED lamp loads of 5 Watt, 10 Watt, and 15 Watt. Parameters measured included input voltage, input current, output voltage, output current, and output frequency. The test results showed that the inverter was able to produce AC output voltages of 219 Volt, 216 Volt, and 211 Volt respectively with frequencies close to 50 Hz. The increase in load caused a slight decrease in output voltage and frequency due to increased current and power losses in the circuit. Overall, the inverter succeeded in converting 12 Volt DC into AC voltage close to household electricity standards and was stable enough for light electrical loads.